Studi Analisis Pengaruh Filter Aktif Berbasis Fuzzy Logic Controller Untuk Mereduksi Harmonisa Akibat Beban Non Linier - Dwi Ade Saputra, G. A. M.; Rinas, I Wayan; Suartika, I Made (Jurnal SPEKTRUM, 2019)
Electrical equipment categorized as the nonlinear load will cause harmonics. Harmonic is a periodic distortion of the sine wave that can cause a negative impact on electronic equipment components. One way to improve power quality is to reduce harmonics using harmonic filters. In this study, an analysis of the system was carried out before adding a filter and after adding an active filter based on a fuzzy logic controller. The application of the fuzzy logic method on filters functions to reduce over switching in the inverter so that it can reach the lowest THDi value. THDi simulation results when the existing conditions are in phase R, S, T; at 14%, 17%, 14%. When the active filter condition is without control, the THDi percentage at the R phase is 6%, the S phase is 6%, the T phase is 4%. In the active filter conditions based on the fuzzy logic controller the percentage of THDi in phase R, S, T; is 0.9%, 0.9, 1%. Based on the simulation results introduced in the active filter based fuzzy logic controller is able to reduce harmonic distortion to the lowest value, so the use of fuzzy logic in active filters can be used in the harmonic filtering process in the electrical system.